Estimation of the Global Distribution of Phytoplankton Light Absorption From Pigment Concentrations. Issue 8 (23rd August 2022) - Soja‐Woźniak, Monika; Clementson, Lesley; Wojtasiewicz, Bożena; Baird, Mark
Abstract: Light absorption by phytoplankton drives marine primary production and determines ocean color. Phytoplankton absorption is a function of the pigment composition, wavelength, intracellular pigment concentration, and the cells' type. This paper presents phytoplankton absorption spectra reconstructed from in situ pigment concentration and a library of pigment‐specific absorption coefficients from 32 individual pigment standards, including chlorophylls, caretonoids and phycobilins. The samples dominated by small phytoplankton show no significant difference between calculated absorption and that measured by a spectrophotometer. The component of absorption due to large cells, determined by diagnostic pigments analysis, required correction for the package effect. For the global ocean, the reconstructed phytoplankton absorption was overestimated by 16% at 443 nm and underestimated by 13% over the range between 400 and 700 nm. Following our reconstruction protocol, this approach allows the estimation of phytoplankton absorption spectra from many locations where pigment concentration has been measured, but no directly observed phytoplankton absorption measurements are available. Plain Language Summary: Phytoplankton, the small plant life of aquatic systems, absorb light which, together with available nutrients, determines their biomass and ultimately the productivity of the ocean or water mass. In situ phytoplankton absorption measurements require specialized equipment and expertise and are therefore infrequent, limiting our understating of aquatic photosynthesis. Photosynthetic phytoplankton contain pigments which are easier to measure using standard equipment and analytical methods. As a result, in situ pigment concentrations are 10 times more common than phytoplankton absorption measurements and are obtained in a wide range of global environmental studies. In this study, we show how to reconstruct the phytoplankton light absorption measurement based on the measurements of pigment composition and concentration. The method was applied to a data set of 8, 012 pigment samples that were collected from all regions of the world's oceans. We then generated a global map of reconstructed phytoplankton absorption which compares well to maps of phytoplankton absorption derived from satellite imagery. Our paper provides a tool which can be used globally by aquatic scientists to convert measurements of pigment concentration into absorption spectra. As a result, light absorption and the maximum photosynthesis by phytoplankton can be accurately estimated for more oceanic areas of the globe. Key Points: Observation of phytoplankton pigment concentration outnumber the in situ measurements of phytoplankton absorption spectra This paper has developed a new technique for reconstructing phytoplankton absorption spectra from pigment concentrations alone Global maps of reconstructed and remotely‐sensed absorption at the chlorophyll a maximum shows similar magnitude and spatial distribution